A Plant‐Produced Candidate Subunit Vaccine Reduces Shedding of Enterohemorrhagic Escherichia coli in Ruminants. Issue 10 (28th September 2017) - Miletic, Sean; Hünerberg, Martin; Kaldis, Angelo; MacDonald, Jacqueline; Leuthreau, Antoine; McAllister, Tim; Menassa, Rima
Abstract : Enterohemorrhagic Escherichia coli (EHEC) are commonly present in the gastrointestinal tract of cattle and cause serious infectious disease in humans. Immunizing cattle against EHEC is a promising strategy to decrease the risk of food contamination; however, veterinary vaccines against EHEC such as Econiche have not been widely adopted by the agricultural industry, and have been discontinued, prompting the need for more cost‐effective EHEC vaccines. The objective of this project is to develop a platform to produce plant‐made antigens for oral vaccination of ruminants against EHEC. Five recombinant proteins were designed as vaccine candidates and expressed transiently in Nicotiana benthamiana and transplastomically in Nicotiana tabacum . Three of these EHEC proteins, NleA, Stx2b, and a fusion of EspA accumulated when transiently expressed. Transient protein accumulation was the highest when EHEC proteins were fused to an elastin‐like polypeptide (ELP) tag. In the transplastomic lines, EspA accumulated up to 479 mg kg −1 in lyophilized leaf material. Sheep that were administered leaf tissue containing recombinant EspA shed less E. coli O157:H7 when challenged, as compared to control animals. These results suggest that plant‐made, transgenic EspA has the potential to reduce EHEC shedding in ruminants. Abstract : Enterohemorrhagic E. coli O157:H7 colonizes cattle and is shed in fecal matter, resulting in meat and environmental contamination. In this study, the authors produced a potential oral vaccine in tobacco plants to prevent colonization of cattle and administered lyophilized leaves to sheep. Shedding of E. coli O157:H7 is somewhat reduced in immunized animals. This is a proof of concept study about the potential for oral immunization of ruminants to improve food safety.